DICOM Image Secure Communications With Internet Protocols IPv6 and IPv4. - Jianguo Zhang (IEEE Transactions on information technology in biomedicine)
Image-data transmission from one site to another through public network is usually characterized in term of privacy, authenticity, and integrity. In this paper, we first describe a general scenario about how image is delivered from one site to another through a wide-area network (WAN) with security features of data privacy, integrity, and authenticity. Second, we give the common implementation method of the digital imaging and communication in medicine (DICOM) image communication software library with IPv6/IPv4 for high-speed broadband Internet by using open-source software. Third, we discuss two major security-transmission methods, the IP security (IPSec) and the secure-socket layer (SSL) or transport-layer security (TLS), being used currently in medical-image-data communication with privacy support. Fourth, we describe a test schema of multiple-modality DICOM-image communications through TCP/IPv4 and TCP/IPv6 with different security methods, different security algorithms, and operating systems, and evaluate the test results. We found that there are tradeoff factors between choosing the IPsec and the SSL/TLS-based security implementation of IPv6/IPv4 protocols. If the WAN networks only use IPv6 such as in high-speed broadband Internet, the choice is IPsec-based security. If the networks are IPv4 or the combination of IPv6 and IPv4, it is better to use SSL/TLS security. The Linux platform has more security algorithms implemented than the Windows (XP) platform, and can achieve better performance in most experiments of IPv6 and IPv4-based DICOM-image communications. In teleradiology or enterprise-PACS applications, the Linux operating system may be the better choice as peer security gateways for both the IPsec and the SSL/TLS-based secure DICOM communications cross public networks